'Labour supply during war-time' - TUC circular, 1940 (pg. 6) (1940)
1940 1939-1945 "'Labour supply during war-time' - TUC circular, 1940 (pg. 6)" [HFR0234f], 1940 In May 1940, the Minister of Labour, Ernest Bevin, appointed a Joint Consultative Committee with representatives from the TUC General Council and the British Employers' Confederation to advise him on wartime industry. This TUC circular briefs affiliated unions on recent activities of the JCC and on the Defence Regulations. Issues covered include: collective bargaining and the regulation of wages, holidays, control of employment and transfers of workers, defence of factories and the post-war restoration of trade union practices.